Pemanfaatan Website Direktorat Jenderal Pajak Oleh Akuntan Pemerintah Di Kalimantan Timur - Subhan, Muhammad; Gafur, abdul (UNIVERSITAS NEGERI SURABAYA, 2014)
AbstractThis research aimed to examine the effect ofperceived usefulness variable, perceived ease of use variable and psychological attachment variable to attitude inusing information technology. Attitude will influence the behavior specifically inutilizing information technology concern shown bythe behavior. Data was obtained through the questionnaire survey with a purposely sampling technique with the criteria, accountants who utilize tax website that www.pajak.go.id in performing their work. Accountants who are being sample do f this study is accountant who are in government organizations. Analysis of the data in this research uses Structural Equation Modeling (SEM) with an alternative method of PLS (Partial Least Square) which is assisted with the application program Smart PLS. Based onthe results of the research be concluded that 1) there is no significant relationship between perceived usefulness and attitude variables in the utilizationof taxwebsite (www.pajak.go.id.); 2) there is asignificant relationship between the variables of perceived ease of use and attitude in the use of website taxation (www.pajak.go.id); 3) there is no significant relationship between the variables of psychological attachment and attitude in the utilization of tax website(www.pajak.go.id); 4) there is asignificant relationship between attitude and behavior variables intention to use the website taxation (www.pajak.go.id).Key Words: perceived usefulness, perceived ease of use, psychologicalattachment, attitude, behavior intention.